Crossing the Hooghly River near Kolkata in India: a tale of two bridges spanning 130 years. Issue 1 (20th September 2021) - Acharya, Pramod Kumar; Kumar, Ajeet; Roy, Partha; Ghose, Prithunandan; Ghoshal, Amitabha
Abstract : A 415 m long three-span steel railway bridge was built over the tidal Hooghly River near Kolkata in India in 2016. The new Sampreeti Bridge is just 22 m downstream from the 1887 Jubilee Bridge it replaces, which is due to be moved to an outdoor engineering heritage museum. Despite 130 years of engineering advances, the forces of nature proved equally challenging to overcome. As happened previously, a pier caisson was swept away by monsoon rains – twice – and accommodating dynamic loading required adoption of the latest bearing technology.